2014
DOI: 10.1371/journal.pone.0105708
|View full text |Cite|
|
Sign up to set email alerts
|

In Situ Measurement of Some Soil Properties in Paddy Soil Using Visible and Near-Infrared Spectroscopy

Abstract: In situ measurements with visible and near-infrared spectroscopy (vis-NIR) provide an efficient way for acquiring soil information of paddy soils in the short time gap between the harvest and following rotation. The aim of this study was to evaluate its feasibility to predict a series of soil properties including organic matter (OM), organic carbon (OC), total nitrogen (TN), available nitrogen (AN), available phosphorus (AP), available potassium (AK) and pH of paddy soils in Zhejiang province, China. Firstly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 34 publications
2
42
1
1
Order By: Relevance
“…Similar results to those studied with SOM and TN were reported in other studies (Table 3). This study had similar results to other studies that had moderately high accuracy of the predicted results especially in paddy field area in a case study in Malaysia and China (Gholizadech et al 2013, Wenjun et al 2014). In addition, other land use types such as the Mediterranean regime with various land uses in Spain and a wheat crop land use in Canada both had high accuracy of SOM prediction, while the predicted TN result in wheat crop area had low accuracy (Martin et al 2002, Zornoza et al 2008).…”
Section: Resultssupporting
confidence: 87%
“…Similar results to those studied with SOM and TN were reported in other studies (Table 3). This study had similar results to other studies that had moderately high accuracy of the predicted results especially in paddy field area in a case study in Malaysia and China (Gholizadech et al 2013, Wenjun et al 2014). In addition, other land use types such as the Mediterranean regime with various land uses in Spain and a wheat crop land use in Canada both had high accuracy of SOM prediction, while the predicted TN result in wheat crop area had low accuracy (Martin et al 2002, Zornoza et al 2008).…”
Section: Resultssupporting
confidence: 87%
“…As can be seen in Table 3, 2 R regression value was found as 0,793 and residual prediction 2 deviation value as 2.0802. R and the RPD values calculated in this study for the prediction of total nitrogen were lower than that of previous studies (Xie et al, 2011;Wenjun et al, 2014). Many researchers have reportedsuccessful application of thevis-NIR spectroscopy for the prediction of various soil characteristics.…”
Section: Resultscontrasting
confidence: 72%
“…In another study, prediction accuracy of total nitrogen with laboratory-based soil spectra using 2 the PLSR method was R of 0.87 and RPD of 2.81 (Wenjun et al, 2014). The successful prediction of soil total nitrogen is mainly due to the nitrogen's direct spectral responses to the overtones and combinations of N-H, C-H+C-H and C-H+C-C in the vis-NIR spectra (Stenberg et al, 2010;Kuang et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In their study, they found soil pH measurements taken in the laboratory to be at 2 'Excellent' level of prediction (R =0.85, RMSEP=0.18 and RPD=2.52), while measurements made in the field were found to 2 be 'very good' (R =0.81, RMSEP= 0.20 and RPD=2.14).As a result, it was concluded that visible and infrared spectrophotometry could be used successfully for the estimation of soil pH. Wenjun et al (2014) used vis-NIR spectrophotometry in field and laboratory in order to determine certain soil properties in 2 plowed land. The R value for soil pH was found as 0.82, while the RPD value was 2.42, and thus by looking at these values, they were able to predict the soil pH with approximate quantitative accuracy.…”
Section: Resultsmentioning
confidence: 95%
“…The RPD evaluation classification for estimating the soil pH performance given in Table 2 suggests that the values of the model succeeded with a moderate level of correlation. According to the reports of Wenjun et al (2014), Williams (2003) and Saeys 2 et al (2005), when the R value was between 0.66 and 0.81 with the RPD value between 2 and 2.5, a 'good' estimation of the examined variable was possible.In a study using visible and nearinfrared spectrophotometry for the purpose of estimating the soil properties of Azerbaijan Mugan soil, the soil pH was found to have 2 a low predictive value according to the obtained R value (Feyziye et al, 2016). Tekin et al (2013) sought to determine the potential of soil pH measurement for deriving the variable rate lime recommendations in the laboratory and on the ground using visible and near infrared spectrophotometry.…”
Section: Resultsmentioning
confidence: 99%